Towards bridging the grey digital divide: changes in internet access and its predictors from 2002 to 2014 in Germany. - Huxhold, Oliver; Hees, Elena; Webster, Noah J. (European Journal of Ageing, 2020)
The internet is an indispensable aspect of modern society. It facilitates long distance communication, access to information, health care interventions, as well as multiple opportunities for social participation. Despite increasing pervasiveness of this technology, persistent inequalities exist in who has access to the internet. In particular, older adults lag behind in having internet access, thus putting them at risk for social exclusion. In order to gain a better understanding about the determinants of this grey digital divide, the current study contrasts influencing factors of internet access, comparing samples from 2002 to 2014 across age groups (40 to 54 years, 55 to 69 years and 70 to 85 years) using data from the German Ageing Survey (DEAS). Logistic regression confirmed that the likelihood of having internet access was lower with higher age at both time points. However, the percentages of people with internet access grew primarily in the middle and older age groups between 2002 and 2014. Furthermore, being male and having a higher education were both associated with greater odds of internet access. However, gender and education differences in internet access were significantly less pronounced in 2014 in contrast to 2002. Finally, both greater income and cognitive ability were associated with greater odds of internet access, while providing care for a grandchild was significantly associated with internet access only among the oldest age group. In an attempt towards bridging the grey digital divide, the current study serves as a basis for identifying groups mostly affected by this increasingly important form of social inequality.